PENGARUH PENDEKATAN BERMAIN TERHADAP MOTIVASI BELAJAR PENJASORKES DI SMPLB-B DHARMA ASIH PONTIANAK - Dwi Riswono; Victor Gaperius Simanjuntak; Andika Triansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2018)
AbstractProblems in this research is learning approach that tends to be centered on the teacher so as to make students less active and easy to get bored in learning and lack of attention of learners to learning penjasorkes.This study aims to determine the effect of play approach to learning motivation learners on subjects penjasorkes in SMPLB-B Dharma Asih Pontianak.The method used in this research is experimental method with research form is true eksperimental design .The research is a population study with the subjects of all learners amounted to 28 students divided into two groups, namely the experimental group and the control group with each group amounted to 14 students .The experimental group given the learning treatment with the play approach. Data collection techniques using observation sheets and interviews. Data analysis technique is t-test with the help of SPSS version 22 .The results showed that there is influence of play approach to learning motivation penjasorkes obtained t-test results Sig.(2-tailed) 0.001 0.05.Then obtained experimental group result of 35,07 bigger than control group equal to 30,07 , percentage of increase equal to 16,63% meaning do not show significant influence. Keywords: Play Approach, Learning Motivation, Student SMPLB-B